Balanced nutrition actions for employees : A cross sectional study - Adha, Andi Syamsiah; Adnan, Yudi; Jusriani, Rini; Jayadi, Yusma Indah; Kahfi, Muhammad (Universitas Islam Negeri Alauddin Makassar, 2024)
One concept of social determinants of health is the workplace. The workplace can be one of the places that can influence health outcomes and risks, function and quality of life. This research examines the prediction model for balanced nutrition actions for employees of UIN Alauddin Makassar. This research is a quantitative research study with a cross-sectional study approach. The research population was all employees, including staff, lecturers, teaching staff and security guards at UIN Alauddin Makassar. The research sample was determined using the one sample situation-about precision formula with a minimum sample of 138 respondents. The total sample in this study was 195 respondents drawn using purposive sampling. This research shows that UIN Alauddin Makassar employees with good practices regarding balanced nutrition are 97.5%, which proves that the percentage of employees who know about balanced nutrition measures is almost the entirety. The results of bivariate analysis showed that the educational variable (p=0.046) had an influence on the balanced nutrition of UIN Alauddin Makassar employees To improve balanced nutritional behavior among employees of UIN Alauddin Makassar, it is necessary to implement ongoing educational programs on balanced nutrition, especially for those with low education levels, as well as provide easy access to healthy foods within the campus environment.